The Image of Geese in Lithuanian Phraseology - Plachovičiūtė, Diana (Tautosakos darbai, 2024)
The article focuses on the image of geese in Lithuanian phraseology, attempting to define its peculiarities and possible connections with other phenomena of the traditional culture. The research material consists of Lithuanian phraseologisms picked out from the lexicographical sources and mentioning either goose, gander, or gosling. Analysis of these phraseologisms reveals that the main peculiarities of the image are related to appearance, character, and behavior of the birds, as well as to the actions performed with them. Phraseologisms emphasize the webbed feet of the geese, their neck, blue gizzard, enlarged reproductive organs, or scabrous skin when deplumed. Geese are depicted as noisy, greedy, oat-eating birds, they waddle in a line, following each other. Their image is not without controversies: they can get wet, but their feathers do not get drenched through. In phraseology, geese are mainly characterized as angry and stupid. The depiction of geese-tending conveys significant cultural information related to the notion of the afterlife, as well as entertainment and economic activities. In general, the image of geese in Lithuanian phraseology is ascribed a negative connotation.
Keywords: the image of geese; phraseology; Lithuanian language; Lithuanian traditional culture